Effect of the Entrepreneurial Propensity on the Human Development of Professionals in the Creative Craft Industry (Gestão & Regionalidade, 2024)
The theme of entrepreneurship in the creative industry became the focus of discussions in international bodies and communities, being identified as strategic for the growth and economic and social development of developed and developing countries, whether through the generation of employment and income, or whether through the promotion of social inclusion, cultural diversity or human development. Based on this assumption, the work analyzes the effect of entrepreneurial propensity on the human development of professionals working in the creative craft industry. A survey was used, applied to 350 respondents. Multivariate analysis techniques and structural equation modeling were used. The results show that the constructs 'need for achievement' and 'strategic posture' positively influenced the construct 'entrepreneurial propensity'; the 'entrepreneurial propensity' construct had a positive effect on the 'human development' construct of professionals working in the creative craft class.
Keywords: Entrepreneurial propensity; Human development; Creative class; Creative industries; Craftsmanship